Evaluation of Micro Credit Providing in The Cash Expenditure Accounting System Based on Banking Credit Procedure Standards at PT Bank Mandiri (Persero)Tbk Manado Area - Diana Nova Lintong; Claudia Korompis (Universitas Sam Ratulangi, 2023)
Providing microcredit